2021
DOI: 10.3390/ijerph18084076
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Quantification of Silver Nanoparticles (Ag-NPs) and Dissolved Ag in Seafood by Single Particle ICP-MS: Assessment of Dietary Exposure

Abstract: This study provides a first insight on the chemical characterization and quantification of silver nanoparticles (AgNPs) and dissolved Ag in processed canned seafood products, where food-grade edible silver (E174) is not intentionally added nor is the nanoparticle contained in the food contact material. The aim was to evaluate the bioaccumulation potential of AgNPs and to contribute to the assessment of AgNPs and ionic Ag human dietary intake from processed seafood. It is known how seafood, and in particular pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…8.2.7 Fish and seafood. Grasso et al 135,136 published 2 papers investigating TiO 2 and Ag nanoparticles in seafood. Multiple samples of canned tuna, mackerel, anchovies and clams were obtained from the local market and digested under alkaline conditions using TMAH, to preserve the integrity of the particles.…”
Section: Applications: Foods and Beveragesmentioning
confidence: 99%
See 1 more Smart Citation
“…8.2.7 Fish and seafood. Grasso et al 135,136 published 2 papers investigating TiO 2 and Ag nanoparticles in seafood. Multiple samples of canned tuna, mackerel, anchovies and clams were obtained from the local market and digested under alkaline conditions using TMAH, to preserve the integrity of the particles.…”
Section: Applications: Foods and Beveragesmentioning
confidence: 99%
“…The sizes of NPs and flakes tended to be slightly larger in food products compared to the actual additive. Grasso et al 135 used spICP-MS to determine the number and size of AgNPs in canned tuna, mackerel, anchovy and clam in order to assess discharge of NPs into the aquatic environment and the implications for human health. Procedures for extraction of NPs and digestion for total Ag measurement were validated and values determined for NP size, diameter, number, total Ag and Ag in NPs.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…A survey has been undertaken for the Ag I and Ag NP content of canned seafood samples, anchovy, clam, mackerel and tuna, available on the Italian market. 170 The analytes of interest were extracted by alkaline hydrolysis, TMAH for 24 hours with initial UAE for 30 minutes at 37 °C followed by dilution with 1% TMAH and analysis by sNP-ICP-MS. The LOD of the method, evaluated using procedural blanks, was 1.5 × 10 3 particles per mL, which equated to 3.3 × 10 5 particles per g after the sample mass and TMAH volumes used were accounted for.…”
Section: Elemental Speciation Analysismentioning
confidence: 99%
“…Another possible transformation of NPs that could occur is the dissolution of them after their uptake (Abbas et al, 2020). In fact, several reports have shown that Ag NPs can undergo either dissolution or sulfidation, or both transformation when they are uptaken by cells/organisms (Moore et al, 2015;Yue et al, 2017;Grasso et al, 2021;Khan et al, 2019). Distinct accumulation patterns to NPs exposure are expected in each organ, which can be associated with the contributions of different organs to the detoxification, excretion or uptake of exogenous substances (Bartucci et al, 2020).…”
Section: Accumulation Of Nps In Tissuesmentioning
confidence: 99%